Depression and Self-Esteem Among Child Sexual Abuse Victims in Malaysia - Ahmad, Nor Shafrin binti; Nasir, Rohany binti (ANIMA Indonesian Psychological Journal, 2008)
This research attempt to identify the level of depression and self esteem among child sex- ually abused victims in Malaysia and also determine the relationship of victims’ depression with their age at the onset of abuse. It also identify differences of depression between victims with different numbers of perpetrators and determine the relationship between victims’ depression and their self es- teem. A majority of subjects (90.7%) were victims of penetrative sexual abuse and 9.3% were mo- lested. Beck Depression Inventory (BDI) and Rosenberg Self Esteem Scale were used to measure de- pression and self-esteem respectively. Results indicate that victims were at critical (32%), moderate (30.7%), mild (21.3%), and minimum (16%) levels of depression; 72% of the victims projected a moderate level of self esteem. Results also reveal a positive significant correlation between age at the onset of abuse and victims’ depression, meaning that older victims were more likely to describe them- selves as being depressed. There are no differences between numbers of perpetrators and victims’ de- pression, which has a negative significant correlation with self-esteem. Penelitian ini mengidentifikasi tingkat depresi dan harga diri pada anak korban pelecehan seksual di Malaysia dan juga menentukan hubungan tingkat depresi korban dan usia saat terjadinya pelecehan, mengidentifikasi perbedaan depresi antara korban dan jumlah penyerang yang berbeda, dan menentukan hubungan antara depresi korban dan harga dirinya. Sebagian besar korban (90.7%) adalah korban perkosaan dan 9.3% korban penganiayaan. Beck Depression Inventory (BDI) dan Rosenberg Self Esteem Scale dipakai berturut-turut untuk mengukur depresi dan harga diri. Hasil menunjukkan bahwa para korban depresinya pada tingkat kritis (32%), moderat (30%), ringan (21%), dan minimal (16%); 72% korban menunjukkan harga diri pada tingkat moderat. Hasil juga mengungkap korelasi positif yang bermakna antara usia awitan pelecehan dan tingkat depresi korban, berarti korban yang lebih tua cenderung lebih merasakan depresi. Tak ada beda antara jumlah penyerang dan depresi korban, yang berkorelasi secara negatif bermakna dengan harga dirinya.